3x-12+2x=-3+14

Simple and best practice solution for 3x-12+2x=-3+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-12+2x=-3+14 equation:


Simplifying
3x + -12 + 2x = -3 + 14

Reorder the terms:
-12 + 3x + 2x = -3 + 14

Combine like terms: 3x + 2x = 5x
-12 + 5x = -3 + 14

Combine like terms: -3 + 14 = 11
-12 + 5x = 11

Solving
-12 + 5x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 5x = 11 + 12

Combine like terms: -12 + 12 = 0
0 + 5x = 11 + 12
5x = 11 + 12

Combine like terms: 11 + 12 = 23
5x = 23

Divide each side by '5'.
x = 4.6

Simplifying
x = 4.6

See similar equations:

| -18-6k=-3(1-3k) | | [x]-6=12 | | (5x+2)3= | | 1.5(x+8)=4.3+0.8x | | 10a-a= | | 18c-29c=151-30 | | 0.6x+1.5=-0.6(2x+5) | | 5(3x-1)+2x+9(2x-3)=5(6x-7)+11x-21 | | 4(-x-2)= | | 19-7p=-8p-(p-7) | | (7p-7)=10(2p+6)-7(-2+2p) | | 5x^4-8x^3-20x^2-4x+3=0 | | -6y+3x=-39 | | 4(y+2)-2(1-y)-4y=0 | | -33=2+5y | | 7(-2y+3)= | | 14+-2x=-3(x+1)-5 | | 55x+5y=45 | | 4(2x+5)+3x-2(x-7)=3(2x+7)-8 | | [Y]=5 | | -3x-2y=-2 | | 3(z-1)= | | 14-2x=-3(x+1)-5 | | 6(3+1)-30=3(2n-4) | | -6y+2y=-104 | | 4x-3+3=12 | | 9x-7=4x+9 | | 3x^2-5x+5=33 | | 10x-35+3x=5x-7a | | N+11=2 | | 2(3+x)=14x | | 11(4-3x)-5(2x+13)=194 |

Equations solver categories